Digital competence in teaching: a case study from a sociocultural perspective - Ruiz-Aday, Yuliedys (2024)
Digital teaching competence (DTC) stands out as a fundamental component in current education, demanding skills for educators to perform effectively in digital environments. The present research aims to analyze the sociocultural influence on the digital competence of teachers of first grade of General Unified Baccalaureate (BGU) of the Fiscal Educational Unit (UEF) 24 de Mayo, Quito, Ecuador, during the first quarter of the 2023-2024 school year. The importance of considering the cultural and social context of teachers in the integration of digital competencies in the planning of the didactic process is highlighted. For this purpose, a mixed methodological approach was used, combining quantitative and qualitative elements that link digital competence with empirical indicators. Participants were selected through purposive sampling. Research techniques such as content analysis of documents, surveys and semi-structured interviews allowed obtaining a comprehensive view of teachers' digital competence and how it is influenced by sociocultural factors present in context. The results reveal that the sociocultural perspective affects the integration of digital competencies, highlighting the need to overcome technological limitations and change perceptions rooted in the educational culture. It is concluded that addressing these challenges from a sociocultural perspective can improve the integration of technology in the teaching of Language and Literature. integration of technology in teaching of Language and Literature.